A Study on Some Variables Which are Related to the Delay of the Morphological Component Development of the Kindergarten Kids’ Language: A Case Study - Alhawarneh, Moammar (Jordan Journal of Educational Sciences, 2019)
This study aims to conduct an individual study for four distinctive cases for highlighting some variables which are related to the delay of the morphological component development of the kindergarten kids’ language, In addition to analyzing some linguistic texts to show some high-profile features of the kids’ speech of this level. The researcher has applied the test of the morphological component of the language on (100) children – male and female- aged between (5-6) years old of the kindergarten kids of Al-Alson School. After that, four kids were chosen- the first and the second who got the highest degrees of the test of the morphological component for the language, and the third and the fourth who got the lowest degrees of the test – and the study was applied on them. The result of the study shows a weakness in the level of intelligence of the affected children in the delay of the morphological component of the language, and the increasing fear of the affected children of the delay of the morphological component of the language, and the decreae of the cultural, social and economic level of the family of the affected children of the delay of the morphological component of the language. Also, there is no difference in the morphological component development of the language according to the difference of sex ’ male or female’, and the language of the affected children of the delay of the morphological component of the language is distinguished with the short-spoken and not detailed replies, existence of silent stops at the beginning of the speech, the shortness of the length of the sentences, the scarcity of vocabularies, Lack of communicative efficiency, scarcity of the using of nouns and a slow average in the speed of speech.